-6(3n-4)=4n+6(4+n)

Simple and best practice solution for -6(3n-4)=4n+6(4+n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3n-4)=4n+6(4+n) equation:



-6(3n-4)=4n+6(4+n)
We move all terms to the left:
-6(3n-4)-(4n+6(4+n))=0
We add all the numbers together, and all the variables
-6(3n-4)-(4n+6(n+4))=0
We multiply parentheses
-18n-(4n+6(n+4))+24=0
We calculate terms in parentheses: -(4n+6(n+4)), so:
4n+6(n+4)
We multiply parentheses
4n+6n+24
We add all the numbers together, and all the variables
10n+24
Back to the equation:
-(10n+24)
We get rid of parentheses
-18n-10n-24+24=0
We add all the numbers together, and all the variables
-28n=0
n=0/-28
n=0

See similar equations:

| 5|y-6|=45 | | F(x+8)=1/4x+5 | | 2(q+5)=15 | | 83x+50=66x+400 | | 3(x-2)+2x=5(x | | (x)+2(x+1)=9 | | 3(x+6)-2(x-2)=10 | | -5(t-5)=7t=6t-2 | | (3/4x)+1=10 | | G(x)=4-7x | | -72=-24+-8j | | 3/13x+1/2=4/9-10/13x+4/9 | | 5c=39.95 | | |x-1|+7=3 | | -6(5z/6+5)=60 | | -x-9=-4x+3 | | x2=-11x-25 | | 4n–3=15 | | X-(x-8)=30 | | 4n–-3=15 | | 19=+4x25 | | 36t=0 | | 1/6x+1=10 | | 1.5g=24 | | -(5/8)w=-9 | | 15-3(4x-9)=-66 | | H=-16t^2+128t+1.5 | | (2−4d)(2+4d)=0 | | 5/6s+3/8=2/3 | | 1x+2x=44 | | -1/3=y-1 | | (x+7)^2=-25 |

Equations solver categories